Harian Kuning dan Media Sensasional Islam - Fanani, Fajriannoor (Jurnal The Messenger, 2012)
Yellow press or yellow journalism is types of journalism that have little concern to accuracy and impartiality. This kind of journalism usually used in many metropolitan newspaper that heavily sensationalized crime, sex, and metaphysical news. This kind of newspaper allegedly also found in some Islamic magazine with its own characteristic, in this case Sabili Magazine. These magazines have some unique journalism characteristic that could be compared to yellow journalism. This is including sensationalist, bombastic, and partisan. This writing tries to show how Sabili magazine used types of journalism that have similarities with yellow journalism.